Assessment of risk factors and preventive measure compliance against COVID-19 among healthcare workers at tertiary care hospital: a retrospective study - Khatoon, Arifa; Aslam, Reema; Bilal, Shabnam; Naz, Sadia; Zaffar, Farhan; Khan, Shahbaz Ahmed; Ramzan, Rao Muhammad; Noreen, Saima; Phoolzaib, Kiran; Batool, Zahra; Saleem, Kahsma; Rasheed, Saba (German Medical Science GMS Publishing House, 2023)
Introduction: SARS-CoV-2 has created a significant challenge to healthcare systems, since the disease has spread rapidly, outweighing hospital capacity and exposing Health Care Workers (HCWs) to the risk of infection. The main objective of this study shows the HCW's self-reported use of Personal Protective Equipment (PPE), symptoms, and exposure to revealed and suspected people during the pandemic, as well as the implementation of infection prevention and control (IPC) guidelines that effectively limit the spread of the infection among healthcare personnel.Method: A single-center retrospective cohort study has been done at a tertiary care hospital. There were 3,651 hospital employees of these 1,890 HCWs and 1,761 nonclinical staff among those who were proven or suspected COVID-19 cases and had symptoms were included. The data was gathered using a standardized self-assessment questionnaire. Information about quarantine protocol and line listing was collected through telephonic conversations.Result: The majority of the participants were males (66%). The average age was 32.1±7.62. Out of 432 HCWs, 32.9% with positive SARS-CoV-2 PCR findings were nurses, 19.2% were doctors, and 47.9% were non-clinical employees from the hospital's inpatient and outpatient departments. 31.5% had a higher-risk exposure, 64.1% had a moderate-risk exposure, and 4.4% of practitioners with COVID-19 had a lower-risk exposure. A statistically significant association was found between COVID-19 disease and adherence to PPE and risk exposure.Conclusion: This study represents the healthcare workers' experience with COVID-19 patients in the early stages of the pandemic and emphasizes the measures required to overcome the problems, however, this study highlights that HCWs are being progressively infected with COVID-19 as a result of inadequate/ inappropriate PPE wear.